The role of the university in knowledge production in order to realize a resistance economy based on knowledge-based economy - Shima Kazemi MalekMahmoodi; Kumars NiazAzari; Negin Jabbari (New Applied Studies in Management, Economics & Accounting, 2021)
Today’s world and its relationships are very complex and variable. This is due to innovation in various academic systems, communications and knowledge-based products. Knowledge-based products are activities in which productivity, resilience and sustainable economy are obtained from the effect of essential knowledge production. The university system is one of the main institutions in determining the quality of information and knowledge-based products. The purpose of this study is to determine the role of the university in achieving a knowledge-based resistance economy. The research method is both qualitative and quantitative. The statistical sample population of faculty members and researchers had an experience of knowledge production during the last three years. The number of samples in the qualitative section was 24 people. In the quantitative part in exploratory factor analysis and confirmatory factor analysis, there were 226 and 156 people, respectively. The method of data collection in the qualitative part of the interview was to categorize the coding and theme process, to extract the items, and in the quantitative part, after validation of 38 items of the researcher-made tool with Cronbach\'s alpha 0.94; In heuristic factor analysis, the appropriate hypotheses of factor analysis, category matrix, common denominator and varimax rotation were used to assign each of the 38 items to 8 factors. According to the findings, 8 dimensions were identified that had a share of about 64%. In the confirmatory factor analysis, the correlation structure confirmed the good fit of the model. These 8 dimensions were; management and institutional system, information and communication technology, efficient resources and facilities, innovation and entrepreneurship in medical sciences, policies and environmental-social effects, structural factors, knowledgebased human resource, registration systems and knowledge-based databases.